Metal Ion Binding in Wild-Type and Mutated Frataxin: A Stability Study - Morante, S.; Botticelli, S.; Chiaraluce, R.; Consalvi, V.; La Penna, G.; Novak, L.; Pasquo, A.; Petrosino, M.; Proux, O.; Rossi, G.; Salina, G.; Stellato, F. (Frontiers in Molecular Biosciences, 2022)
In this work we study the stability of wild-type frataxin and of some of its variants found in cancer tissues upon Co$^{2+}$ binding. Although the physiologically involved metal ion in the frataxin enzymatic activity is Fe$^{2+}$, as it is customarily done, Co$^{2+}$ is most often used in experiments, since Fe$^{2+}$ is extremely unstable owing to the fast oxidation reaction ${Fe}^{2+} → Fe^{3+}$. Protein stability is monitored following the conformational changes induced by Co$^{2+}$ binding as measured by circular dichroism, fluorescence spectroscopy as well as melting temperature measurements. The stability ranking among the wild-type frataxin and its variants obtained in this way is confirmed by a detailed comparative analysis of the XAS spectra of the metal-protein complex at the Co K-edge. In particular, a fit to the EXAFS region of the spectrum allows to positively identify the frataxin acidic ridge as the most likely location of the metal binding sites. Furthermore, we are able to give an explanation of the surprising feature emerging from a detailed analysis of the XANES region of the spectrum showing that the longer 81-210 frataxin fragment has a smaller propensity for Co$^{2+}$ binding than the shorter 90-210 one. This fact is explained by the peculiar role of the N-terminal disordered tail in modulating the protein ability to interact with the metal.